2021
DOI: 10.1186/s12989-021-00429-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface charge-dependent mitochondrial response to similar intracellular nanoparticle contents at sublethal dosages

Abstract: Background Considering the inevitability for humans to be frequently exposed to nanoparticles (NPs), understanding the biosafety of NPs is important for rational usage. As an important part of the innate immune system, macrophages are widely distributed in vital tissues and are also a dominant cell type that engulfs particles. Mitochondria are one of the most sensitive organelles when macrophages are exposed to NPs. However, previous studies have mainly reported the mitochondrial response upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Collectively, it was observed that Au-NPs elicited mitochondrial dysfunction, leading to cell apoptosis and necrosis. However, AuNPs of different surface properties showed distinct effects on mitochondrial alterations, including reduced tubular mitochondria, damaged mitochondria, increased reactive oxygen species, and decreased adenosine triphosphate [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, it was observed that Au-NPs elicited mitochondrial dysfunction, leading to cell apoptosis and necrosis. However, AuNPs of different surface properties showed distinct effects on mitochondrial alterations, including reduced tubular mitochondria, damaged mitochondria, increased reactive oxygen species, and decreased adenosine triphosphate [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria, the energy factories of eukaryotes, generate ATP through the mitochondrial respiratory chain and OXPHOS processes, providing macrophages with the majority of their cellular energy. , Mitochondria also play a role in macrophage-mediated immunity . Given that triclosan causes a shift in energy metabolism from OXPHOS to glycolysis and inhibits TCA in macrophages, it is crucial to understand how triclosan affects mitochondrial activity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, gold nanoparticles as small molecules and drug conjugates enhance targeting with adequate release kinetics. Moreover, the mounting evidence of nanoparticle size and surface charge determines their innate behavior in a biological system and intracellular fate. For instance, the ability of hybrid gold nanoparticles with modified shapes to deliver doxorubicin is remarkable. In this aspect, elongated (nanorods) and spiky (nanoprisms) gold nanoparticles are mostly appropriate for biomedical applications. …”
Section: Introductionmentioning
confidence: 99%